THE ROLE OF PARENTS AS CO-FACILITATORS IN A HYBRID LEARNING PROGRAM FOR EARLY CHILDHOOD LITERACY AND NUMERACY - Amir Raza; Jamil Khan; Roya Zahir (Journal Neosantara Hybrid Learning, 2026)
The shift toward hybrid education models has redefined parental roles in early childhood learning, particularly in literacy and numeracy development. This study investigates the function of parents as co-facilitators within a hybrid learning program designed for children aged 4–6 years in Indonesian preschools. The research responds to the growing need for parental engagement in digital-assisted instruction, especially following the pandemic’s acceleration of home-based learning. The main objective is to evaluate how structured parental involvement influences children’s literacy and numeracy outcomes when supported by hybrid pedagogical strategies. A mixed-method design was employed, combining quantitative assessment of 120 children’s progress across three learning cycles with qualitative interviews involving 40 parents and 10 teachers. Instruments included performance rubrics for literacy and numeracy, digital activity logs, and parent reflection journals. The data revealed that children whose parents acted as co-facilitators demonstrated a 28% higher improvement in early literacy and a 24% increase in numeracy mastery compared to peers with minimal parental support. Qualitative findings underscored the importance of parental scaffolding, consistency in learning routines, and emotional engagement as critical mediators of learning success. The study concludes that hybrid learning programs in early childhood education are most effective when parents are equipped and empowered to function as co-facilitators rather than passive observers. The integration of family-centered design principles within digital learning ecosystems enhances not only academic performance but also socio-emotional resilience and motivation among young learners.